Efektivitas Expressive Writing dalam Menurunkan Kecemasan pada Mahasiswa - Putri, Emilya Dwinata; Afiful Adrian,; Della Oktari,; Raudhatul Fitri,; Aflah Zakinov Irta, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aimed to determine the effectiveness of expressive writing in reducing anxiety among students at Padang State University. This study employed a quantitative approach. It employed a between-subject design and a pretest-posttest control group design. The sample consisted of 17 students majoring in Psychology at Campus V, Padang State University. Based on the results, it can be concluded that expressive writing activities are effective in reducing anxiety levels. The independent sample t-test analysis showed a significance value of 0.030 (p < 0.05), indicating a significant difference between the experimental group participating in the expressive writing intervention and the control group participating in regular writing. These findings indicate that through expressive writing, students can convey and process their negative emotions, thereby reducing psychological tension and improving emotional balance. Therefore, expressive writing can be a simple yet effective therapy method to help students overcome anxiety, especially in stressful academic situations such as public speaking.